Meningkatkan Kualitas Pelayanan Publik Melalui Reformasi Birokrasi - Anwaruddin, Awang (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2004)
During the last two decades, the issues of public service have been arising all over the world. Triggered by the concept of Reinventing Government (Osborne & Gaebler, 1992), the US Government launched a project with the same term as the concept in 1995. In the beginning of 1990, the UK Government announced the Next Steps as the government effort to fulfil the basic needs of the citizen. Other commonwealth countries, such as Australia, New Zealand and Singapore followed the steps in various terms, all intended to improve the public service (Osborne & Plastrik, 1996).In most cases, the low quality of public institution in facilitating various kinds of service has generated such spirit of reinventing public service. People in Indonesia have long suffered from the sluggish and extended bureaucratic chain, which causes high-cost service in the process of attaining the driver license, passport, marital and birth certificates, letters of land belongings, and other formal documents. The similar phenomena appear in the service of telephone network, electricity, clean water, education, health service, transportation and other public services.The government of Indonesia has actually published various kinds of policy concerning the improvement of public service quality. Published during the Soeharto era were alternately The Guidance of Simplification and Control of Business Permit (1984), The Guidance of Public Service Management (1993), and The Guidance of Reorganization and Improvement of Government Apparatus Service to the Society (1995). After the Reformation era, the government announced The Real Steps to improve Public Service (1998) and finally the General Guidance of Public Service Implementation(2003).